Convergence of modified homotopy perturbation method for Fredholm-Volterra integro-differential equation of order m - Eshkuvatov, ZK; Zulkarnain, FS; Muminov, Z; Long, NMAN (PENERBIT UTM PRESS, 2024)
Indexed by WOS